Examining the Impacts of CO(2) Concentration and Genetic Compatibility on Perennial Ryegrass—Epichloë festucae var lolii Interactions - Geddes-McAlister, Jennifer (J Fungi (Basel), 2020)
Perennial ryegrass (Lolium perenne) is the most cultivated cool-season grass worldwide with crucial roles in carbon fixation, turfgrass applications, and fodder for livestock. Lolium perenne forms a mutualism with the strictly vertically transmitted fungal endophyte, Epichloë festucae var lolii. The fungus produces alkaloids that protect the grass from herbivory, as well as conferring protection from drought and nutrient stress. The rising concentration of atmospheric CO(2), a proximate cause of climatic change, is known to have many direct and indirect effects on plant growth. There is keen interest in how the nature of this plant–fungal interaction will change with climate change. Lolium perenne is an obligately outcrossing species, meaning that the genetic profile of the host is constantly being reshuffled. Meanwhile, the fungus is asexual implying both a relatively constant genetic profile and the potential for incompatible grass–fungus pairings. In this study, we used a single cultivar, “Alto”, of L. perenne. Each plant was infected with one of four strains of the endophyte: AR1, AR37, NEA2, and Lp19 (the “common strain”). We outcrossed the Alto mothers with pollen from a number of individuals from different ryegrass cultivars to create more genetic diversity in the hosts. We collected seed such that we had replicate maternal half-sib families. Seed from each family was randomly allocated into the two levels of the CO(2) treatment, 400 and 800 ppm. Elevated CO(2) resulted in an c. 18% increase in plant biomass. AR37 produced higher fungal concentrations than other strains; NEA2 produced the lowest fungal concentrations. We did not find evidence of genetic incompatibility between the host plants and the fungal strains. We conducted untargeted metabolomics and quantitative proteomics to investigate the grass-fungus interactions between and within family and treatment groups. We identified a number of changes in both the proteome and metabalome. Taken together, our data set provides new understanding into the intricacy of the interaction between endophyte and host from multiple molecular levels and suggests opportunity to promote plant robustness and survivability in rising CO(2) environmental conditions through application of bioprotective epichloid strains.